Influence of biochar amendment on growthattributes of Sapindus mukorossi Gaertn.: A sustainable approach for agroforestrydevelopment - Pandey, Kamya; Melkania, N.P.; Arunachalam, A; Bisht, Lalita; Tripathi, Shivangi (Indian Journal of Agroforestry, 2025)
This study explores influence of pre-sowing seed treatments and biochar application on the growth and vigour of Sapindus mukorossi Gaertn. seedlings. Various combinations of biochar (soil, sand, FYM, and biochar) were applied in different ratio, alongside pre-sowing treatments, to evaluate their possible impacts on seedling growth attributes, such as, height, collar diameter, root length, leaf area, fresh and dry weight, and vigour indices like root: shoot ratio, sturdiness quotient, and seedling vigour index (SVI). The results revealed significant variations in seedling growth and vigour among different treatments. Biochar, particularly when combined with sand, demonstrated positive effect on seedling growth, enhancing root and shoot development, leaf area, and overall seedling quality. The study suggests that biochar can play a crucial role in enhancing seedling establishment, particularly in nursery settings for S. mukorossi. The findings point the potential of biochar as a valuable substance for enhancing seedling quality in forestry, agroforestry and land restoration projects. Future research is recommended to assess the long-term effects of biochar on soil health, species-specific responses, and its economic feasibility for sustainable environmental management.